Functions of GUANXI and its changing significance for Singapore businesses operating in China. - Lee, Imm. (2008)
This project investigates the functions of guanxi and its changing significance for Singapore businesses operating in China. It also looks at the difference in the use of guanxi between Singapore and China. It also explains how guanxi can be maintained. Lastly,it presents some negative aspects of guanxi.